Marsilea minuta L. (Marsileaceae): new occurrence for the Brazilian Amazon - Tavares, Jorgeane Valéria Casique; Kikuchi, Tatiani Yuriko Souza; Maciel, Sebastião; Almeida Lins, Alba Lúcia Ferreira de (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2014)
Marsilea minuta L. (Marsileaceae) is reported for the first time in the Brazilian Amazon. It’s an aquatic fern introduced in Brazil that occurs in anthropogenic environments. The morphological and anatomical characteristics of plants from aquatic and terrestrial environments were described and illustrated.